2011
DOI: 10.1021/jp208361p
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid/Metal–Organic Framework Composite for CO2 Capture: A Computational Investigation

Abstract: A composite of ionic liquid [BMIM][PF6] supported on metal–organic framework IRMOF-1 is investigated for CO2 capture by molecular computation. Due to the confinement effect, IL in the composite exhibits an ordered structure as observed from radial distribution functions. The bulky [BMIM]+ cation resides in the open pore of IRMOF-1, whereas the small [PF6]− anion prefers to locate in the metal cluster corner and possesses a strong interaction with the framework. [BMIM]+ exhibits a greater mobility than [PF6]−, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
118
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 46 publications
6
118
1
Order By: Relevance
“…[8][9] IL-MOF combinations have been considered recently in the gas separation field. [10][11][12][13][14][15][16] For instance, Chen et al 17 incorporated IRMOF-1 composite and reported a CO 2 /N 2 selectivity of 70 at ambient conditions. To understand the effect of different types of ILs on the separation performances of IL-MOF systems, ILs with the same cations but different anions were studied.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9] IL-MOF combinations have been considered recently in the gas separation field. [10][11][12][13][14][15][16] For instance, Chen et al 17 incorporated IRMOF-1 composite and reported a CO 2 /N 2 selectivity of 70 at ambient conditions. To understand the effect of different types of ILs on the separation performances of IL-MOF systems, ILs with the same cations but different anions were studied.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38] Some experimental and theoretical studies have shown that MOFs could be used as potential porous supporter for ILs. [39][40][41][42][43][44][45][46] Jiang and co-workers 42 first investigated the IL/IRMOF-1 composites for CO 2 /N 2 separation by molecule simulation, showing that the selectivity can be enhanced when introducing ILs into the pores of IRMOF-1. Later, this group further computationally explored the capabilities of MOF-supported IL membranes for CO 2 /N 2 separation in which the effect of 5 anions of ILs and the role of hydrophobic/hydrophilic framework were examined.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk molar composition of the mixture was taken as H 2 S:CH 4 =0.001:0.999 (i.e., 1000 ppm of H 2 S), which can represent a typical concentration of H 2 S in crude natural gas 59. As done by others,42,45 the structures of all the IL/Cu-TDPAT composites were treated as rigid during adsorption simulations. Actually, we have done some…”
mentioning
confidence: 99%
“…Most of the studies regarding gas adsorption properties of MOF-supported ILs have been mainly computational simulations [141][142][143][144]. A composite of [BMIM][PF 6 ] IL supported on IRMOF-1 was investigated for CO 2 capture by molecular computation by Chen and coworkers [141].…”
Section: Computational Studiesmentioning
confidence: 99%
“…A composite of [BMIM][PF 6 ] IL supported on IRMOF-1 was investigated for CO 2 capture by molecular computation by Chen and coworkers [141]. The [BMIM] + cation resided in the open pores of IRMOF-1, while the small [PF6] -anion was located in the metal cluster corner interacting strongly with the framework.…”
Section: Computational Studiesmentioning
confidence: 99%